2019
DOI: 10.1504/ijram.2019.103334
|View full text |Cite
|
Sign up to set email alerts
|

Risk management in carbon capture and geological storage: insights from a structured expert elicitation

Abstract: With a focus on risk management (RM) in injection and storage for carbon capture and geological sequestration (CCS), an expert elicitation of scientific judgements quantified collective uncertainty ranges for a number of difficult environmental and human health risk challenges. Results suggest similarities and differences in opinions, an outcome that may be reflective of both the newness and the complexity of this technology. A suitable monitoring period was estimated at about a century; however, uncertainty w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For CCS activities (capture, transportation, well drilling, CO 2 injection, short-term and long-term storage), Sarkarfarshi et al (2019, Supplementary Information) provide a database of potential events, including a short description, the occurrence probability, magnitude and potential adverse consequence(s). Larkin et al (2019aLarkin et al ( , 2019b provide findings from a structured expert elicitation on relative risk and uncertainty judgements for potential hazards in injection and storage and risk management of low probability high impact (LPHI) events. As an outstanding issue for CCS, Koornneef et al (2012) suggested that ongoing uncertainty in injection and storage components of integrated projects has the potential to become a bottleneck for wide-scale implementation of CCS, if not properly addressed.…”
Section: Economic Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…For CCS activities (capture, transportation, well drilling, CO 2 injection, short-term and long-term storage), Sarkarfarshi et al (2019, Supplementary Information) provide a database of potential events, including a short description, the occurrence probability, magnitude and potential adverse consequence(s). Larkin et al (2019aLarkin et al ( , 2019b provide findings from a structured expert elicitation on relative risk and uncertainty judgements for potential hazards in injection and storage and risk management of low probability high impact (LPHI) events. As an outstanding issue for CCS, Koornneef et al (2012) suggested that ongoing uncertainty in injection and storage components of integrated projects has the potential to become a bottleneck for wide-scale implementation of CCS, if not properly addressed.…”
Section: Economic Costsmentioning
confidence: 99%
“…In tabular format, potential risk management options within each of the five REACT categories, as they may apply to value-chain activities, are provided in the supplementary material [online]. These options were identified from research by Larkin et al (2019a) and Larkin et al (2019cLarkin et al ( , 2019d concerning the features of RA/RM frameworks worldwide, analysis of regulatory practice in the Canadian context and findings from an expert elicitation, as well as research reported in Gale et al (2015). The suggestions cover wide-ranging approaches to be discussed and accepted within the risk management context in which the project is proposed.…”
Section: Risk Management Options For Ccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important dimension to this issue is the complexity of the risk assessment for CCS, which is a function of the multi-dimensional aspect of the technology (i.e., the integration of capture, transport, injection and storage). This complexity demands a response in terms of prioritisation of the relative severity of various impact scenarios, especially those which are high-impact, low-probability cases (Larkin et al, 2019c;Sarkarfarshi et al, 2019).…”
Section: Adequate Risk Assessment and Risk Management Frameworkmentioning
confidence: 99%
“…Nevertheless, placing realistic quantitative bounds on event probability and consequence remains a highly contentious process for several reasons, mainly because of a lack of experiential history in the area of georisk, critically important for long-term security. Larkin et al (2019aLarkin et al ( , 2019b discuss findings from a structured expert elicitation on relative risk and uncertainty judgements for potential hazards in injection and storage, and risk management of low probability high impact events.…”
Section: Introductionmentioning
confidence: 99%